Jawabanmu

2014-08-19T20:38:22+07:00

g(x) = ax + b
g(5) = 8
g(5) = 5a + b
5a + b = 8

g(x) = ax + b
g(2) = -1
g(2) = 2a + b
2a + b = -1

Eliminasi b

5a + b = 8
2a + b = -1
--------------- -
3a = 9
a = 3

5.(3) + b = 8
15 + b = 8
b = -7

Jadi a = 3 b = -7



1 1 1
2014-08-19T20:39:53+07:00
G(x)=ax+b
g(5)=a.5+b-------> 5a+b=8
g(2)=a.2+b-------> 2a+b=-1 -
                        ----------------
                          3a    =9
                               a =9/3   
                               a =3

5a+b=8
5.3+b=8
15+b=8
     b=8/15
     b=0,34


1 1 1